THE ROLE OF STRATEGIC COLLABORATION IN IMPROVING SUPPLIER PERFORMANCE: A BUYER-SUPPLIER PERSPECTIVE IN A REGIONAL-OWNED ENTERPRISE IN DKI JAKARTA - Hasrul, Hasrul; Limankrisna, Nandan; Muharam, Hari (Yayasan Education and Social Center, 2025)
This study aims to examine the role of strategic collaboration in improving supplier performance in DKI Jakarta Regional-Owned Enterprises (BUMD) from a buyer-supplier perspective. Strategic collaboration is considered the key to success in supply chain management, especially in the context of business relationships between buyers and suppliers. Qualitative research methods were used with data collection through in-depth interviews with procurement managers and key suppliers in several BUMDs in DKI Jakarta in the period November 2024 to January 2025. The results of the study indicate that the three main dimensions of collaboration, communication, trust, and technology, play an important role in improving supplier performance. Transparent and intensive communication helps synchronize operations, trust strengthens supplier loyalty and commitment, while technology supports the efficiency of procurement and monitoring processes. This study confirms that strengthening strategic collaboration is an effective strategy to improve sustainable supplier performance in the BUMD environment. Practical implications of this study include the need to improve communication, build a culture of mutual trust, and utilize technology in supply chain management.